2003
DOI: 10.1021/es034380a
|View full text |Cite
|
Sign up to set email alerts
|

Space-Use Strategy Is an Important Determinant of PCB Concentrations in Female Polar Bears in the Barents Sea

Abstract: Space-use was examined in 54 female polar bears (Ursus maritimus) from Svalbard and the Barents Sea that were collared with satellite transmitters to provide information on their spatial positions and annual home range sizes. Plasma samples from the same animals were analyzed for concentrations of six relevant PCB congeners (PCB-99, -153, -156, -180, -194, and -118). Factors related to space-use strategy (such as home range size; annual, spring, and winter longitudinal position; and spring and summer latitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 49 publications
1
35
2
Order By: Relevance
“…Although a previous study based on telemetry movements of collared individuals suggested that pelagic females (with large home ranges) were located farther south than nearshore females (with smaller home ranges), it showed no differences in body mass between both groups (Olsen et al, 2003). Further studies should investigate differences in body condition between females of each ecotype.…”
Section: Effects Of Sampling Location On Body Conditionmentioning
confidence: 74%
“…Although a previous study based on telemetry movements of collared individuals suggested that pelagic females (with large home ranges) were located farther south than nearshore females (with smaller home ranges), it showed no differences in body mass between both groups (Olsen et al, 2003). Further studies should investigate differences in body condition between females of each ecotype.…”
Section: Effects Of Sampling Location On Body Conditionmentioning
confidence: 74%
“…Aroclor 1254, in the polar bear food chain (Letcher et al, 1995;de March et al, 1998). However, biological factors such as regional variation in diet, food chain structure, and biotransformation ability could also affect the bioaccumulation/biomagnification pattern for these classes of lipophilic compounds Norstrom et al, 1988;Olsen et al, 2003). Inversely, western polar bear populations of the North American Arctic were characterized by a significantly higher exposure to relatively volatile compounds such as HCHs and PnCBz, and tri-to penta-chlorinated PCB congeners, suggesting a stronger influence of Southeast Asian and North Americansourced inputs for these classes of contaminants (Iwata et al, 1993;Macdonald et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, systematic surveys of the geographical distribution of CHCs in polar bears have been undertaken throughout most of the Arctic and Subarctic regions, and an extensive database of CHC measurements is available from the 1980s and 1990s, and of measurements dating as far back as late 1960s Norheim et al, 1992;Norstrom and Muir, 1994;Letcher et al, 1995Letcher et al, , 1998Bernhoft et al, 1997;Norstrom et al, 1998;Andersen et al, 2001;Norstrom, 2000;Kucklick et al, 2002;Derocher et al, 2003;Lie et al, 2003;Olsen et al, 2003;Dietz et al, 2004, Sandala et al, 2004. To date, the highest degree of contamination among circumpolar polar bear populations has been reported from the western Russian Arctic, followed by Svalbard Andersen et al, 2001;, whereas the lowest concentrations of contaminants were reported from Alaska (Bering/Chukchi Sea) polar bear samples Kucklick et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Movement behaviour further complicates the issue. For example, Olsen et al (2003) explained differences in contaminant levels as a result of varying activity seen in small versus large home range sizes in Barents Sea polar bears.…”
Section: Pcb Contaminationmentioning
confidence: 99%
“…It has been documented that contaminants have negative effects on thyroid hormones, sex steroid homeostasis and the immune system of marine mammals, including polar bears (Haave et al 2003;Olsen et al 2003;Oskam et al 2003;Braathen et al 2004;Lie et al 2004Lie et al , 2005Oskam et al 2004;Letcher et al 2010). Acting on quite different scales, sea-ice changes and human disturbance may reduce access to food or increase energy expenditure by making hunting less effective (including by reducing prey) or increasing the distances polar bears need to walk or swim.…”
Section: Stressors and Cumulative Effectsmentioning
confidence: 99%